1997
DOI: 10.1139/g97-117
|View full text |Cite
|
Sign up to set email alerts
|

Molecular marker based taxonomy and phylogeny of Guinea yam (Dioscorea rotundataD.cayenensis)

Abstract: Four different molecular techniques were used to assess relationships among 21 accessions of Guinea yam (Dioscorea rotundata and Dioscorea cayenensis) and 21 accessions belonging to seven putative progenitor species. Random amplified polymorphic DNA (RAPD) and microsatellite-primed PCR (MP-PCR) analysis yielded 246 informative characters that were transformed into a matrix of pairwise distances and analyzed by neighbor joining or split decomposition. Both methods gave congruent results. Well-separated groups w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 34 publications
2
24
0
3
Order By: Relevance
“…Both types of assay were carried out in a total volume of 17 l, including 0.9 U Taq DNA polymerase (QIAGEN) in the reaction buffer system supplied by the manufacturer (including 1ϫ Q-Solution to reduce scoring problems due to DNA secondary structures) and final concentrations of 2-5 mM MgCl 2 , 0.2 mM dNTP, 0.8 M primer, and 2-25 ng of template DNA. Amplifications were performed in a PerkinElmer 9700 thermocycler under the cycling conditions described by Ramser et al (1997) , banding profiles were resolved on 1.5% agarose gels in TBE buffer (Sambrook et al, 1989), stained with ethidium bromide, and photographed under UV light with a red filter. Homology of comigrating bands was exemplarily tested by Southern blot hybridization (Ramser et al, 1997).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both types of assay were carried out in a total volume of 17 l, including 0.9 U Taq DNA polymerase (QIAGEN) in the reaction buffer system supplied by the manufacturer (including 1ϫ Q-Solution to reduce scoring problems due to DNA secondary structures) and final concentrations of 2-5 mM MgCl 2 , 0.2 mM dNTP, 0.8 M primer, and 2-25 ng of template DNA. Amplifications were performed in a PerkinElmer 9700 thermocycler under the cycling conditions described by Ramser et al (1997) , banding profiles were resolved on 1.5% agarose gels in TBE buffer (Sambrook et al, 1989), stained with ethidium bromide, and photographed under UV light with a red filter. Homology of comigrating bands was exemplarily tested by Southern blot hybridization (Ramser et al, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…Amplifications were performed in a PerkinElmer 9700 thermocycler under the cycling conditions described by Ramser et al (1997) , banding profiles were resolved on 1.5% agarose gels in TBE buffer (Sambrook et al, 1989), stained with ethidium bromide, and photographed under UV light with a red filter. Homology of comigrating bands was exemplarily tested by Southern blot hybridization (Ramser et al, 1997). For this, two individual RAPD and two MP-PCR bands were excised from the gel, each purified with a QIAquick Gel Extraction Kit (QIAGEN), reamplified with the respective primer, and labeled with 32 P by random priming (Sambrook et al, 1989).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors consider them as part of a complex called D. cayenensis/D. rotundata (Dansi et al, 1999;Mignouna et al, 2002), while others consider them as two distinct species (Ramser et al, 1997;Mignouna et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of phylogenic studies using RFLP analysis in chloroplast and nuclear ribosomal DNA, it was suggested that D. cayenensis is a variety of D. rotundata (Terauchi et al, 1992). More recent studies based on isozyme (Dansi et al, 2000a) and molecular markers (Ramser et al, 1997;Mignouna et al, 1998Mignouna et al, , 2005 support the separate identity of the two species.…”
Section: Discussionmentioning
confidence: 99%